Kepatuhan terhadap peraturan PPh final jasa kontruksi pada perusahaan kontruksi di Indonesia - Bilqist Putri Arievani; Susilawati (Jurnal Akuntansi dan Manajemen, 2026)
This research examines Indonesian construction businesses' compliance with the Final Income Tax on construction services, as governed by Article 4, paragraph (2), of the Income Tax Law, from 2020 to 2024. The study is driven by persistent tax compliance challenges in the construction sector, notwithstanding its important contribution to national economic development. This study aims to investigate the impact of corporate tax knowledge, tax regulations, and tax penalties on Final Income Tax compliance in the construction industry. This study uses an explanatory research design and a quantitative methodology. Panel data regression was used to analyze secondary data from the annual financial statements of 11 construction businesses listed on the Indonesia Stock Exchange. The findings reveal that tax regulatory comprehension, company awareness, and tax penalties have a substantial influence on tax compliance among construction enterprises. This study empirically contributes to the literature on sector-specific tax compliance. It offers practical implications for tax authorities and construction enterprises for enhancing compliance with the Final Income Tax laws